Exploring institutional collaborative culture and task accomplishment in industrial settings: A case study of industries in Iran - Nazari Poor, Erfan; Zahedi, Mohammadreza (Annals of Management and Organization Research, 2024)
Purpose: This study explores the dynamics of institutional collaborative culture and its influence on task accomplishment in industrial contexts. Using a correlational design, it investigated variables such as teamwork, dynamic support, delegation of responsibilities, and organizational norms and values in relation to task completion. Research Methodology: This study targeted a population of 200 principal officers from diverse departments within industries in Iran. Data collection employed a modified Likert-scale instrument focused on Institutional Collaborative Culture and Task Accomplishment in Iranian industries. The sampling was stratified, resulting in a sample size of 110 participants. Data analysis included mean, standard deviation, and regression techniques. Results: The findings indicated a significant correlation between the elements of institutional collaborative culture (teamwork, dynamic support, norms, and values) and task accomplishment. However, delegation of responsibilities did not demonstrate a significant relationship with task completion. Recommendations: This study proposes promoting teamwork principles and providing comprehensive support to personnel across all levels of industrial operations as essential strategies for enhancing task accomplishments within industrial settings.